Pengaruh Supervisi Kepala Sekolah dan Etos Kerja Guru terhadap Kinerja Guru Al-Kausar Boarding School Sukabumi - Ian Cantona; Imam Tholkhah; Amie Primarni (Jurnal Dirosah Islamiyah, 2023)
Human Resources (HR) is the main factor in an agency. Whatever the purpose, the organizational structure is made based on various visions for the benefit of humans and in carrying out its mission it is managed and implemented by humans. In this study, the human resources meant are teachers, schools would really like to have teachers who have high performance, but in fact there are still some problems that are found that show low teacher performance, after observations found that supervision activities and teacher work ethic are considered to be factors that affect teacher performance. can improve the performance of Al-kausar boarding school teachers. This study aims to determine: 1) The effect of principal supervision on teacher performance, 2) The effect of teacher work ethic on teacher performance, 3) The influence of principal supervision and teacher work ethic on teacher performance.The approach used in this research is quantitative. The research location was conducted at Al-Kausar Boarding Shool Sukabumi with sampling technique. This technique includes saturated samples. Saturated sample is the determination of the sample if all members of the population are used as samples. Data collection techniques in this study use documentation, and interviews and questionnaires are distributed, one of which uses a form to the respondents. Then the hypothesis is tested by means of a simple regression test and then a multiple regression test. Based on statistical calculations 1) Principal's supervision has no effect on teacher performance at Al-Kausar Boarding School Sukabumi, this is evidenced by the results of the t test which obtains a t count of -1.426 which is smaller than the t table of 2.042, besides that there is also a significant value of 1, 61 is greater than 0.05 so it can be concluded that the hypothesis Ho is accepted. 2) The work ethic of teachers affects the performance of teachers at Al-Kausar Biarding School Sukabumi, this is evidenced by the t-count value of 3.261 which is greater than t-table 2.042, besides that the significance value of 0.002 is smaller than 0.05, so it can be concluded that the null hypothesis Ho is rejected. Principal supervision (X1) and teacher work ethic (X2) simultaneously have a positive effect on the teacher performance variable (Y). Because the significance shows 0.003 < 0.05, then Ho is rejected and Ha is accepted. In addition, 24.1% teacher performance is influenced by the supervision of the principal and the teacher's work ethic together Keywords: Principal Supervision, Work Ethic, Teachers, Teacher Performanc